ENTRADA NA PROFISSÃO: ESCOLHA PESSOAL OU IMPOSIÇÃO SOCIAL? - Cava, Antonio Olegário Blanco (2013)
The study seeks to identify the factors that contribute to career choice for students at the end of high school, whether the choice based on some program-specific professional guidance, or following guidance from family, friends, teachers or professionals, or is just a situational imposition, depending on youth s social class. One can find several answers, depending on the socioeconomic status occupied by the individual; for each portion of the population, may occur the reproduction of his or hers socioeconomic context, since the factors that influence that choice may vary among different society strata. The literature research includes authors such as Pierre Bourdieu, Jean-Claude Passeron, Mary Alice Nogueira and Alipio Casali, among others. The study is completed with a field survey in which respondents were students from two high school institutions, respectively from public and private networks, both located in the city of São Bernardo do Campo (SP). It is, therefore, a literature and qualitative research. Empirical data were collected through the application of a questionnaire to direct responses, and also of an open question, so that the students involved would contribute new elements for the final analysis.